Traditional Treatment Practices Of Fractures In Banda Aceh - Rasyida, Azzahra Oya; Fikarwin Zuska (Indonesian Journal of Medical Anthropology, 2022)
The choice of traditional medicine methods as an alternative to treatment is becoming increasingly popular, especially with the recommendation to return to nature. One of the traditional medicine practices that is still often used is the treatment of fractures. This thesis describes the practice of fracture treatment in Banda Aceh City by a broken herbalist, and reveals the factors that cause patients to choose the traditional treatment of fractures. The thesis was written based on ethnographic field research with data collection techniques for in-depth interviews and observations of fracture shamans and patients treated by the broken shaman. The results of this study show that traditional medicine has been carried out for generations. Treatment is carried out using decoctions derived from traditional herbs and spices. The healing process in the practice of fractures is divided into two, namely the healing of light fractures and the healing of severe fractures. A mild fracture takes a short healing time of approximately about a week. As for severe fractures, it takes approximately three months. Patients who have fractures prefer traditional medicine over medical due to economic, social, and cultural factors.